Treatment of abdominal aortic pseudoaneurysm caused by brucellosis with endovascular aneurysm repair - Li, Xiao; Wang, Qilong; Zhang, Yang; Sun, Xiwei; Yin, Hang; Zhang, Hua; Luo, Sean X.; Wang, Zhongying; Yu, Qi; Chen, Zhiming; Cheng, Zhihua (Frontiers in Bioengineering and Biotechnology, 2023)
Peripheral vascular disease caused by brucellosis is rarely seen around the world; thus, it is easily ignored by patients and doctors, leading to a lack of corresponding screening and delayed comprehensive treatment. Currently, there is no standard or guideline for diagnosing and treating peripheral arterial disease caused by brucellosis. From June 2021 to December 2022, four cases of abdominal aortic pseudoaneurysm caused by brucellosis disease were treated with endovascular aneurysm repair (EVAR). This study reported treatment results as follows and reviewed the incidence, treatment, and prognosis of abdominal aortic pseudoaneurysm caused by brucellosis.